2023
DOI: 10.32598/ijvm.17.4.1005354
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Azithromycin Toxicity in Chickens and Quails

Yamama Z Al-Abdaly,
Mohammed Younis Alfathi,
Saevan Saad Al-mahmood

Abstract: Background: The pharmacologic and toxicological response to different drugs vary according to the type and breed of the animal. Objectives: This investigation was carried out to compare the toxic effects of azithromycin on chickens and quails. Methods: The animals of each kind were divided into 3 groups; the first group served as the control and received just distilled water; the second and third groups received different doses of azithromycin (5% and 10% of the median lethal dose) over 5 days. Results: Compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…This release is accomplished by activating NADPH oxidase, the primary cause of testicular oxidative stress. TNF-α also inhibits several antioxidant enzymes, including superoxide dismutase and catalase, increasing the testicular state of oxidative stress (Alnuaimi & Alabdaly, 2023;Al-Abdaly et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…This release is accomplished by activating NADPH oxidase, the primary cause of testicular oxidative stress. TNF-α also inhibits several antioxidant enzymes, including superoxide dismutase and catalase, increasing the testicular state of oxidative stress (Alnuaimi & Alabdaly, 2023;Al-Abdaly et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Az is commonly employed to treat lower respiratory tract bacterial infections and boost immunity against bacterial diseases in poultry [37]. At higher dosages of Az, Al-Abdaly et al [38] observed neurotoxic effects on the brains and livers of chick and quail specimens. The available data on Az's toxicological effects and safe dosage in poultry are inadequate.…”
Section: Discussionmentioning
confidence: 99%
“…At 8 h and 3 day post-treatment, histopathological findings indicate hepatocyte degeneration, congestion, and sinusoidal dilation. Increased drug doses intensify liver damage [38]. These alterations could be due to direct drug toxicity leading to degeneration and necrosis.…”
Section: Discussionmentioning
confidence: 99%